Targeting Copper Dysregulation In Cancer: Molecular Insights Into Cuproptosis and The Promise of Copper-Based Nanomedicine - Srivastava, Aditi; Shahma, Abu; Sharma, Jyoti Nanda (Journal of Neonatal Surgery, 2025)
Copper is an essential transition metal that plays a vital role in cellular metabolism as a cofactor for key enzymes. While necessary for biological processes such as mitochondrial respiration, antioxidant defense, and gene expression, copper must be tightly regulated to prevent cytotoxicity. This review investigates copper homeostasis at both cellular and systemic levels, highlighting the significance of dietary intake, absorption, transport, and excretion. Dysregulation of copper can lead to cell death, especially in cancer cells, through mechanisms such as cuproptosis, a newly recognized form of copper-induced cell death. Cuproptosis involves mitochondrial copper accumulation, disrupting protein function, and triggering cell death. The study explores how copper imbalance contributes to cancer progression, metastasis, drug resistance, and immune evasion. Therapeutic approaches targeting copper metabolism are discussed, including the use of copper chelators and copper-based nanomaterials to improve cancer treatment. Although cuproptosis has sometimes been misinterpreted as the result of ionophore-induced nanoparticle formation, it stems from mitochondrial copper toxicity. The review further evaluates the emerging role of copper nanotechnology in sensitizing tumors to chemotherapy, offering a promising strategy to overcome drug resistance. Overall, the findings underscore copper’s dual role in health and disease and its potential as a therapeutic target in oncology.